INCOME OVER FEED COST (IOFC) DAN NILAI EFISIENSI DALAM FORMULA RANSUM DENGAN PENGGUNAAN TEPUNG USUS AYAM SEBAGAI PENGGANTI TEPUNG IKAN PADA AYAM KAMPUNG FASE PERTUMBUHAN - Kaharuddin, Kaharuddin; Churriyah, A. Ni’mahtul (Ensiklopedia of Journal, 2024)
The superiority of animal protein makes the industry or livestock business has great potential to grow, because Indonesia's low meat consumption can still be increased. This study aims to determine the Income Over Feed Cost (iofc) and the value of ration efficiency with the use of chicken intestine flour as a substitute for some fish flour in the ration formula in the growth phase of native chickens. The research was conducted in the farmer's cage in Lolu Village, Biromaru Subdistrict, Sigi Regency. This research will be designed using a completely randomized design (CRD) with 5 treatments and 4 replications. Data obtained from all observed variables will be calculated using analysis of variance. The results of the analysis of variance showed that the treatment gave no significant effect (P>0.05) on Income Over Feed Cost in native chickens. The treatment gave no significant effect (P>0.05) on the efficiency of ration utilization in native chickens. The treatment gave no significant effect (P<0.05) on the cost of production of native chickens. The treatment gave no significant effect (P>0.05) on the income of local chickens. Based on the results of the study, it can be concluded that the use of chicken intestine meal as a substitute for some fish meal in the ration formulation gives no significant effect on Income Over Feed Cost and ration efficiency value. Based on the results of the study, it is necessary to conduct further research on the provision of chicken intestine flour as poultry feed.